Eco-Anim: Animated Learning Media to Enhance Student Outcomes in Ecology and Biodiversity - Eka Sabila Adilia Yahya Putri; Ratna Wahyu Wulandari; Atika Anggraini (PALAPA, 2025)
This study addresses the challenge of low student learning outcomes in abstract science topics, specifically Ecology and Biodiversity among Grade VII students at MTsN 1 Kota Kediri. The research aims to develop and evaluate an innovative digital learning medium, Eco-Anim, an animated video designed to improve students’ conceptual understanding. Employing the Research and Development (R&D) methodology, the study follows the ADDIE model, encompassing the phases of Analysis, Design, Development, Implementation, and Evaluation. Validation by subject matter and media experts confirmed the feasibility of Eco-Anim, with scores of 91.4% and 87.1% respectively, while user responses were highly positive at 93.2%. An effectiveness test, based on pretest and posttest comparisons, demonstrated significant learning gains, with an average N-Gain score of 0.7991, indicating high effectiveness. Developed using the Animaker platform and integrated with interactive quizzes via Quizizz, Eco-Anim successfully enhanced student engagement and comprehension. The findings suggest that visually engaging and interactive digital media can serve as effective tools for improving science education, particularly in abstract content areas.